Integrated Interpretation of Magnetic and ERT Data to Characterize a Landfill in the North-West of Cologne, Germany - Ibraheem, Ismael M.; Tezkan, Bülent; Bergers, Rainer; Institute of Geophysics and Meteorology, University of Cologne, Cologne, Germany (Pure and Applied Geophysics, 2021)
Electrical resistivity tomography (ERT) and ground magnetic surveys were applied to characterize an old uncontrolled landfill in a former exploited sand and gravel quarry in an area to the north-west of the city of Cologne, Germany. The total magnetic field and its vertical gradient were recorded using a proton precession magnetometer to cover an area of about 43,250 m2. The magnetic data were transferred to the frequency domain and then reduced to the north magnetic pole. The amplitude of the analytical signal was calculated to define the magnetic materials within and outside the landfill. Eight ERT profiles were constructed based on the results of the magnetic survey using different electrode arrays (Wenner, dipole–dipole, and Schlumberger). In order to increase both data coverage and sensitivity and to decrease uncertainty, a non-conventional mixed array was used. The subsurface resistivity distributions were imaged using the robust (L1-norm) inversion method. The resultant inverted subsurface true resistivity data were presented in the form of 2D cross sections and 3D fence diagram. These non-invasive geophysical tools helped us to portray the covering soil, the spatial limits of the landfill, and the depth of the waste body. We also successfully detected low resistivity zones at deeper depths than expected, which probably be associated with migration pathways of the leachate plumes. The findings of the present study provide valuable information for decision makers with regards to environmental monitoring and assessment. Volkswagen Foundation http://dx.doi.org/10.13039/501100001663 Universität zu Köln (1017)